2020
DOI: 10.13106/jafeb.2020.vol7.no10.1007
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Employee’s Intention to Use Information System: Technology Acceptance Model and Information System Success Model Approach

Abstract: This study aims to understand the determinant of the employee's intention to use information system within the framework of the Technology Acceptance Model (TAM) and Information System Success Model (ISSM). This paper also aims to examine the influence of ISSM dimension on the perceived usefulness and the perceived ease of use. The research respondents were 248 employees of Universitas Negeri Semarang (UNNES) who are users of the Financial Information System (SIKEU). Data was obtained using a questionnaire tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 28 publications
2
13
0
2
Order By: Relevance
“…In general, the better the quality of information presented by IT, the easier it is for users to use the technology (C. C. Chen & Tsai, 2019; Martono et al, 2020). A possible explanation for this is that during the VR-based teaching process, the information quality of VR technology is first perceived by students, not teachers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the better the quality of information presented by IT, the easier it is for users to use the technology (C. C. Chen & Tsai, 2019; Martono et al, 2020). A possible explanation for this is that during the VR-based teaching process, the information quality of VR technology is first perceived by students, not teachers.…”
Section: Discussionmentioning
confidence: 99%
“…The regression model supported the hypothesis that "the information quality of VR technology will positively influence teachers' perceived usefulness" but rejected the hypothesis that "the information quality of VR technology positively affects teachers' perceived ease-of-use," which contradicts most ISSM studies. In general, the better the quality of information presented by IT, the easier it is for users to use the technology (C. C. Chen & Tsai, 2019;Martono et al, 2020). A possible explanation for this is that during the VR-based teaching process, the information quality of VR technology is first perceived by students, not teachers.…”
Section: Major Findingsmentioning
confidence: 99%
“…Other areas of study, such as a financial information system in an Indonesian university by Martono et al (2020), an electronic record management system in Yemen's oil and gas industry (Hawash et al, 2021), and a personalized location-based mobile tourism application (C.-C. Chen & Tsai, 2019), showed that system quality had an indirect effect on users' intentions through perceived usefulness. Likewise, the perceived usefulness of a branded sports mobile app mediates the influence of the app's quality and also its content or information on its usage intention among participants from several fitness centers and sports parks in Korea (Won et al, 2022).…”
Section: Perceived Benefits Of Mkmsmentioning
confidence: 99%
“…Performance expectancy is defined as a way to determine the extent to which someone believes using technology will follow the desired expectations (Subawa et al, 2021). Research by Martono et al (2020),…”
Section: Performance Expectancymentioning
confidence: 99%